O performador atômico e o processo de criação em cadeia - Fernando Borges Barcellos (2013)
The chain creative process proposes an approach between certain elements that permeate the performing arts - such as the randomness and self-oriented risk - and quantum physics atomic model, in which the atomic performer is the creatorcrafter the catalyzes the human body potentialities. The creation of the notion of the atomic performer represents a path through which it is possible to go beyond thesuperficial metaphors that relates art and science, making easier the author s individual creative process. In the chain creative process the creator, an atomic performer, can react, such as an atom, through the manipulation of your elementary properties, participating of creative reactions that originate molecular expressive materials. From the discussion of some conceptual and historical concepts related toperformance and the performing arts an image of the artist as a performer was built, and relations were woven between such image and the quantum mechanics atomic model, consolidating the notion of the atomic performer. Both the author's experience in the creative processes of Grupo Oficcina Multimédia (Belo Horizonte - MG - Brazil) and Maldita Companhia de Investigação Teatral (Belo Horizonte - MG - Brazil), and some principles of two creative processes used by Brazilian artisticcollectives, the collective creative process and the collaborative creative process, where definitive to the elaboration of the chain creative process, whose steps where thoroughly discussed. Another important notion to the understanding of this process, the notion of the conceptual teaser, was introduced. In December 2011 the performance Reatividade Atômica (Atomic Reactivity) was presented as the result of the execution of the chain creative process involving a group of four atomicperformers. Inherent elements of the work of the atomic performers during the chain creative process of the performance Reatividade Atômica were discussed based on the photo and video registers of the performance, the audiovisual and textual archives of the creative process and the testimonials of the atomic performers.